Contents of total carbon, inorganic carbon, organic carbon, and total nitrogen as well as Corg/Ntotal values of sediment core GeoB24366_1 from Calabrian accretionary prism (R/V Sonne cruise SO278) - Thomas Pape; Janice Malnati; Yiting Tseng; Gerhard Bohrmann (PANGAEA, 2024)
Shallow sediment cores were collected with a gravity corer from several sites at the Sartori Mud Volcano in the Calabrian accretionary prism during cruise SO278 with R/V SONNE. In order to determine Corg/Ntot values (orgainc carbon/total nitrogen), as well as contents of total carbon, inorganic carbon and organic carbon, sediment samples were taken from the sediment cores with cut-off syringes and transferred into glass vials. The sediment samples were analyzed with a vario EL III elemental analyzer (Elementar Analysensysteme GmbH). Contents of organic carbon were determined after removal of inorganic carbon through acidification.